End-of-life incineration of nanocomposites: new insights into nanofiller partitioning into by-products and biological outcomes of airborne emission and residual ash. Issue 8 (29th June 2018) - Pourchez, J.; Chivas-Joly, C.; Longuet, C.; Leclerc, L.; Sarry, G.; Lopez-Cuesta, J.-M.
Abstract : The assessment of nanofiller partitioning into by-products is a key point to understand the biological outcome of airborne emission and residual ash from the incineration of nanocomposites. Abstract : Since the recycling of nanocomposites is limited, nanofillers will inevitably enter the waste stream. To date, the major end-of-life scenario of nanocomposites is their incineration. This process can strongly affect the pristine physico-chemical features of nanofillers inducing a potential alteration of their initial toxicity. Besides, the partitioning of nanofillers into the subsequent formation of by-products ( i.e. airborne emission and residual ash from the incineration of nanocomposites) remains uncertain. Through laboratory-scale incineration of nanocomposites (an ethylene vinyl acetate matrix incorporating silica, alumina or boehmite nanofillers), we assessed in vitro the potential hazard of the released particulate matter (PM) in combustion exhaust and of the resulting bottom ash. We also fully characterized the physico-chemical and morphological properties of associated by-products. Our findings demonstrated that the partitioning of nanofillers is mainly into residual ash rather than into combustion aerosol. Our results also showed that the hazard profile of the PM seems mainly governed by the intrinsic hazard profile of the host polymer matrix, while the hazard profile of the residual ash seems mainly governed by the intrinsic hazard profile of the pristine nanofillers. Even if the results can depend on the nanofiller chemistry and loading as well as the polymer composition of the matrix, we support the conclusion that a key safety priority to be addressed on the incineration of nanocomposites is to more deeply investigate the potential physico-chemical transformations of nanoparticles in slags and the hazard assessment of residual ash.